Estudio sobre el uso de antibióticos en centros de atención veterinaria de pequeños animales de la ciudad de Loja - Ibarra Armijos, Kevin Alexis (2024)
Improper use of antibiotics in domestic animals can lead to antimicrobial resistance (AMR), which is a problem for both animal welfare and public health. In humans, it can result in ineffective treatments and risks of infectious disease transmission, while in animals it impacts food safety, increasing morbidity and mortality. Therefore, this study aimed to determine the extent of antibiotic use in small animal veterinary care centres in the city of Loja. A survey was applied to 40 veterinary professionals from veterinary care centres (veterinary practices, clinics, and hospitals) to identify the perception and patterns of antibiotic use. The results indicated that 87.5% of participants strongly agreed on the importance of their role in the protection of public health. Furthermore, 60% stated that antibiotic prescription should only be carried out by specialist veterinarians and 78% agreed that using the literature provides greater certainty in the choice of a drug for treatment. Finally, 75% stated that providing educational programmes to veterinarians, non-veterinary advisors, and owners would promote the control, regulation, and management of antibiotics. In conclusion, it was found that there is improper use of antibiotics by owners and non-veterinary advisors due to a lack of education and knowledge, which could lead to antimicrobial resistance in the long term. Keywords: AMR, antibiotics, small animals, public health.